2009
DOI: 10.1371/journal.pbio.1000013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of Polycomb and Trithorax Chromatin Landscapes in Drosophila Embryos

Abstract: Polycomb group (PcG) and trithorax group (trxG) proteins are conserved chromatin factors that regulate key developmental genes throughout development. In Drosophila, PcG and trxG factors bind to regulatory DNA elements called PcG and trxG response elements (PREs and TREs). Several DNA binding proteins have been suggested to recruit PcG proteins to PREs, but the DNA sequences necessary and sufficient to define PREs are largely unknown. Here, we used chromatin immunoprecipitation (ChIP) on chip assays to map the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
380
2
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(413 citation statements)
references
References 51 publications
28
380
2
3
Order By: Relevance
“…S5). These findings are consistent with genome-wide studies showing that both proteins preferentially localize to PREs but are not found at high levels elsewhere in silenced domains (19,26,29,30). We next examined the association of PH and dSfmbt under conditions in which constitutive expression of GAL4 from the tubulin promoter disrupts the silencing activity of the bxdPRE.…”
Section: Transcriptional Read-through Reduces But Does Not Eliminate supporting
confidence: 85%
See 2 more Smart Citations
“…S5). These findings are consistent with genome-wide studies showing that both proteins preferentially localize to PREs but are not found at high levels elsewhere in silenced domains (19,26,29,30). We next examined the association of PH and dSfmbt under conditions in which constitutive expression of GAL4 from the tubulin promoter disrupts the silencing activity of the bxdPRE.…”
Section: Transcriptional Read-through Reduces But Does Not Eliminate supporting
confidence: 85%
“…The PRC1 complex PC protein specifically interacts with histone 3 trimethylated at K27 (H3K27me3), the nucleosome mark stably associated with PcGrepressed chromatin (30,31). Unlike other PRC core components, the distribution of PC and H3K27me3 in PcG silenced domains is not limited to the PRE but instead extends outward from the PRE (26,30,31). We obtained similar results: ChIP experiments indicate that PC and H3K27me3 are associated with transgene sequences to either side of the PRE including white gene (Fig.…”
Section: Pc (Prc1) and H3k27me3 Remain Associated With Bxdpre In Thesupporting
confidence: 56%
See 1 more Smart Citation
“…PcG proteins regulate many targets, including genes encoding proteins that function throughout development (17,18). Some of the pleiotropic phenotypes of Ogt mutants may thus be a consequence of improper silencing of PcG targets, although our data do not rule out other roles for OGT and O-GlcNAc modification in the many important cellular processes linked to OGT function.…”
Section: Discussioncontrasting
confidence: 57%
“…To determine whether the addition of O-GlcNAc residues by OGT might act in concert with PcG protein binding to downstream target genes, we used an anti-O-GlcNAc antibody for in situ analysis of polytene chromosomes. This antibody was chosen because the available anti-OGT (17,18), and suggests that 1 or more PcG proteins could be candidate substrates. The resolution of in situ hybridization is not sufficient to show that OGT acts at the known sites of PcG protein binding, the PcG response elements (PREs).…”
Section: Colocalization Of O-glcnac Protein Modification and Pcg Bindmentioning
confidence: 99%